GOOD CORPORATE GOVERNANANCE DALAM MENINGKATKAN KINERJA PERUSAHAAN - Suzanto, Boy (Majalah Bisnis & IPTEK, 2021)
Transparency, accountability, responsibility, independence and fairness are the basis for the company to develop relationships with stakeholders who have interests in the company's operations. This includes customers, suppliers, creditors, employees and the communities in which it operates. It is necessary to maintain a balance between efforts to meet the interests of shareholders and stakeholders. For that we need a set of corporate governance aspects relating to internal and external balance. Corporate governance is the process and structure used to direct and manage the business and affairs of the company. The goal of course improve the performance and accountability of the company, in order to realize the added value for shareholders in the long term, with due regard to the interests of other stakeholders. Keywords: corporate governance; performance